(untitled) (Al-Qamar, 2022)
In the world of mystic poetry, Ibn Arabi is a key figure, regarded as the pioneer of “wahdat al-wujud” concept. Ibn Arabi frequently elaborates his poetic concepts and thoughts on Sufism through natural symbols. Ibn Arabi’s thoughts on poetic Sufism are written in symbolic Arabic poetry. Through symbolism he usually deploys natural symbols, known as al-ramz in Arabic poetic literature. These symbols reflect something and have some other meaning behind them. The symbolism “al-ramziyyah” is a method used by Arabic poetry and prose to express feelings in mind and conscious.The said Article raises following questions: The relationship of Sufism to poetic experience? What symbols are in Ibn Arabi’s poetries? To answer these questions, the paper applies qualitative methodology by using primary and secondary resources in research because for example Ibn Arabi used the symbols of sun in poetry to represent God as the main source of universe. This article aims to trace the origins of some key concepts of Ibn Arabi’s poetic mysticism in earlier Andalusian Sufi masters.